HUBUNGAN BERPIKIR KRITIS DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PADA SISWA KECANDUAN GAME ONLINE DI SEKOLAH DASAR - Fetrimen, Fetrimen; Wisastra, Darajatun (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2024)
The massive online games on cell phones have an impact on critical thinking and motivation learning student. Student addicted online games lack of concentration understand lessons so that learning outcomes not according achievement assessment standards. This research aims to analyze linkages critical thinking and motivation with learning outcomes on student addicted online games. This research uses approach quantitative.The survey method uses non-causal techniques. The research sample was taken from respondents through a survey of 100 educators by filling out questionnaire likert scala model. The data analysis method in research uses correlational statistical analysis techniques. The research results illustrate linkages critical thinking and motivation with learning outcomes for students addicted online games. The conclusion of this research explains learning outcomes students addicted online games not according achievements competency because linkages critical thinking and motivation student in learning of weak and implications for implementation of learning process for students addicted online games.